"Psychological characteristics of functional respiratory disorders in children and adolescents—Pilot study". Issue 12 (26th September 2022) - Niggemann, Bodo; Maas, Ronja; Suerbaum, Claudia; Spindler, Thomas; Kohl, Andreas; Koerner‐Rettberg, Cordula; Burghardt, Roland
Abstract: Background: Aim of our prospective, multicenter, nonrandomized study was to identify characteristic features and similarities of patients with functional respiratory disorders regarding socio‐familial and behavioral aspects, in comparison with controls in a cross‐sectional analysis using standardized psychological questionnaires. Furthermore, we investigated the longitudinal outcome of symptoms, effects of primary interventions and the stability of psychological traits 6 months after diagnosis and primary intervention. Methods: Initially, 106 patients (68 females, 27 males) and 58 controls (33 females, 25 males) were recruited for the study. Mean age was 12.6 years in patients and 11.9 years in controls. Results: The child behavior checklist (CBCL) showed significantly increased scores for anxious/depressed ( p = 0.002) and schizoid/obsessive ( p = 0.001) behavior in patients. A trend was evident for internalizing behavior ( p = 0.009) and for a higher total score ( p = 0.008). In the self‐assessment youth self‐report (YSR), there was a trend towards higher values for anxious/depressed behavior in patients ( p = 0.06) and towards more externalizing behavior ( p = 0.029) in the control group. After 6 months, 31% of the patients were free of symptoms, 42% had improved. For themselves, parents reported a decreased burden from 56% to 23% ( p < 0.001) and decreased impairment from 57% to 30% ( p < 0.008). For their children, parents reported a decrease from 45% to 16% ( p < 0.0001) and from 74% to 37% ( p < 0.0001), respectively. A longitudinal comparison from T1 to T2 showed no statistically significant changes in all three psychological questionnaires (CBCL, YSR, and SOMS‐KJ). Conclusions: In summary, we show that patients with functional respiratory disorders differ from healthy subjects, with internalizing behavior being a characteristic trait. The outcome in terms of symptoms, perceived psycho‐familial burden and impairment after 6 months is encouraging. However, we are aware that our preliminary data offer thought‐provoking impulses rather than firm findings.